(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This short review focus on pre-prosthetic preparation and rehabilitation of patients who have limb amputation. The father of the prosthesis limb is Ambrosia Pare. He discovered the term prosthesis on 4 November 1846 the prosthesis limbs came from the mind of biomedical Engineering which are made up of Acrylic Resin, Carbon Fibre, Thermoplastic Silicone Aluminium Titanium, etc. They play the main role to improve motion movements and rehabilitation of the joints that’s why they are also used to improve rehabilitation in the prosthesis limb. In medicine a prosthesis or prosthetic implant is an artificial device that replace a missing body part, which may be lost through trauma, disease, or a condition present at birth. Prostheses are intended to restore the normal functions of the missing body part. It is an functional replacement for an pegleg in most case the patient should get died due to excessive amount of surgery and medical treatment, physiotherapy leads to enhance the muscle spasm and also use to give strength.